Maintenance of air conditioner / Muhamad Fauzi Hashim - Hashim, Muhamad Fauzi (Universiti Teknologi Mara, Perak, 2016)
Gerbang Nusajaya Sdn Bhd originated from beginning operating as a class ‘F’ contractor specializing in maintenance work since 1989. Gerbang Nusajaya Sdn Bhd was located at Taman Kempas Utama, Kempas, Johor and the company fully manage by Bumiputera. Since then, the company has grown into a dynamic civil engineering and construction company providing vital support to key industrial sectors such as infrastructure development, building, construction, telecommunication and M&E works. The company had obtained a class ‘A’ Bumiputera Building and Civil Engineering contractor registered with Pusat Khidmat Kontraktor (PKK) as well as a G7 contractor with the Malaysia Construction Industry Development Board (CIDB). It is therefore in a strategic position to bid for a substantial range of projects from both the Government and Private sector.